درجة توفر متطلبات التعليم الأخضر الداعم للمواطنة البيئية (دراسة ميدانية في مدارس محافظة طرطوس) (Journal of Hama University, 2025)
The research aimed to identify the degree of availability of green education requirements that support environmental citizenship in schools in Tartous Governorate from the point of view of teachers, as well as to identify the differences between the average grades of the research sample members according to the variable type of education (general, private). To achieve the objectives of the research, the researcher adopted the descriptive approach and a questionnaire from the researcher prepared a tool for collecting data, consisting of (32) items distributed over five basic axes: (requirements related to school administration, requirements related to infrastructure, requirements related to human capabilities, requirements related to curricula and methods, requirements related to community participation). As for the research sample, it consisted of (527) male and female teachers from schools in Tartous Governorate in the 2024/2025 academic year, the results were analyzed using the statistical program (SPSS), and the results were as follows:• The degree of availability of green education requirements that support environmental citizenship in the schools of Tartous Governorate is medium, with an arithmetic mean of (2.66). The axis of requirements related to school administration ranked first with an arithmetic mean of (2.92), and the axis of requirements related to community participation ranked second with an arithmetic mean of (2.89). Third is the axis of requirements related to human capabilities with a mean of (2.75), while in fourth place is the axis of requirements related to curricula and methods with a mean of (2.39), and in last place is the axis of requirements related to infrastructure with a mean of (2.32).• There are no statistically significant differences at the level of significance (0.05) between the average scores of school teachers’ answers to a questionnaire that provides requirements for green education that supports environmental citizenship according to the type of education variable, with the exception of the axes of infrastructure requirements and community participation requirements, in favor of special education schools.In light of the results obtained, the current research suggested the necessity of designing and implementing specialized training programs for teachers aimed at enhancing their understanding of the concepts of green education and sustainable environmental practices, and improving and modernizing the infrastructure of schools, including providing green spaces, the use of renewable energy sources, the application of waste management systems, the necessity of reviewing school curricula to include sustainable environmental content that enhances environmental awareness among students, and enhancing the role of the local community in supporting green education by organizing joint environmental activities, such as afforestation campaigns, cleaning public areas, and environmental workshops